Chitosan-based Magnetic Particles as Adsorbents for Anionic Contaminants - Kloster, Melina (2023)
An environmentally friendly nano-sized adsorbent with good adsorption capacity for ionic contaminants, that can be easily removed from treated water, was obtained. The adsorbent consists in iron oxide magnetic nanoparticles coated with chitosan, resulting in a core-shell structure. The particles were obtained by a two-step procedure that includes the synthesis of the magnetic core nanoparticles by the alkaline co-precipitation method, followed by their immersion in a dilute chitosan solution. They were characterized and the presence of the organic coating was verified using different techniques. The adsorbent properties were studied using Congo red (CR) solutions, as an example of common ionic adsorbates discharged into the waste streams by textile industries. Adsorption kinetics studies at different CR concentrations and adsorption equilibrium isotherms at two pHs are reported and modeled theoretically. The pseudo-second-order model was the one that best fitted the adsorption kinetics and for equilibrium studies, the best fit was with either the Langmuir model (pH 7) or the Freundlich model (pH 3). The dye adsorption at lower pH was higher than that exhibited by neutral solutions, attributed to the increase in electrostatic attraction between the negatively charged dye molecule and positively charged amine group of chitosan. Preliminary results for CR desorption are also reported.